An Investigation of the Biomechanical and Social Influences of Head-Acceleration Events, and Concussion Management in Women’s Rugby - FREJA PETRIE (2024)
Women are increasingly participating in rugby, a full-contact team sport. This contact acts as a source of exposure to repeated head-acceleration events and concussion, yet strategies to reduce this exposure, or improve concussion management are often developed from male/men’s data. This is despite the numerous sex-and-gender differences that limit the generalisability of male/men’s data and resultantly, the efficacy of subsequently developed interventions. Therefore, this thesis explored the biomechanical, and sociological factors that may influence how women’s rugby players are exposed to head-acceleration events, and how concussions are managed.Study One analysed video footage of two playing levels of university women’s rugby to identify relationships between tackle technique and exposure to head-impact events (HIEs). Players who did not maintain neck positioning during landing, or landed supine were significantly more likely to experience a head-to-ground HIE, or HIE, respectively.Studies Two and Three contextualised the findings of Study One, through the qualitative investigation of player’s concussion history, resource access, and rugby-playing experience. Concussion misconceptions were identified and players expressed a desire for further information pertaining to concussion recovery. Women were less able to access resources than men and were negatively impacted by preconceptions of their playing ability and belonging in the sport.Study Four investigated the feasibility of introducing a neck-strengthening intervention to a university women’s rugby team. Neck-strength improvements were elicited, and stakeholder interviews provided feedback from which future interventions could be improved.This thesis has contributed novel findings to the literature, providing insights that can inform future strategies to minimise head-acceleration event exposure and improve concussion management. Strategies to reduce head-to-ground HIE and address the endemic sexism in rugby should be considered an area of research priority to protect player welfare.